Influence of recycled aggregates and carbon nanofibres on properties of ultra-high-performance concrete under elevated temperatures. (June 2022) - Amin, Mohamed; Hakeem, Ibrahim Y.; Zeyad, Abdullah M.; Tayeh, Bassam A.; Maglad, Ahmed M.; Agwa, Ibrahim Saad
Abstract: Research interest in producing sustainable ultra high performance concrete (UHPC) has been increasing recently. This paper focuses on the use of recycled coarse aggregate (RCA) as a replacement for 50% of the total natural coarse aggregate (NCA). Two types of replacements were used, namely, carbon nanofiber (CNF) with 0.25%, 0.5%, 0.75%, and 1% by weight of binder and steel fibers (SFs) with 0.5%, 1.0%, 1.5% and 2% of by weight of the binder. In addition to this, hybrid fibers, i.e. a combination of CNF with SFs were also used for few mixes. Twenty-six mixtures were prepared to evaluate the engineering properties of UHPCs containing RCA and NCA with CNF and SFs. The mechanical properties were evaluated through tests of the compressive, split tensile, and flexural strengths and the modulus of elasticity. The mass and compressive strength losses were examined to evaluate the effect of UHPC exposure to elevated temperatures (200 °C, 400 °C, 600 °C, and 800 °C). The incorporation of NCF, SFs, and RCA negatively affected the workability, and the diameter of the slump flow was reduced to 230 mm for RCF0. 25-SF2.0 mixture. The addition of fiber contributed to the improvement of the concrete properties. The compressive strengths were 151.3 and 146.9 MPa for the NF0 and RF0 mixtures, respectively. In fiber addition to UHPC, the best improvement was achieved at 164.9, 158.6, 158.8, 153.5, 167.9 and 180.9 MPa for the NCF0.5, RCF0.5, NSF2.0, RSF2.0, NCF0.25-SF2.0 and RCF0. 25-SF2.0 mixtures.